Povezava med objektivno izmerjeno okvaro in bolnikovo oceno kakovosti lastnega življenja po poškodbi kolena pri športu - Marn-Vukadinović, Duša (Rehabilitacija (Ljubljana), 2011)
Background: Rehabilitation process requires insight into the health consequences as perceived by the patients in addition to the assessment of impairments by clinician-based measures. Objective: The study was designed to assess relations among various knee measurements and activity, and health-related quality of life. Methods: One-hundred- one adult subjects after unilateral sport knee injury were involved. Correlations of clinical measurements (tight muscle atrophy, knee range of motion, knee muscle strength) with activity (tested with Oxford Knee Score) and eight subscales of the Short Form Health Survey-36 were estimated. Results: General health and mental health were not related to impaired body structure and function after sport knee injury. Strong relationship between perceived activity and body pain was demonstrated and activity was highly associated with participation in social life. We observed a weak relationship between knee muscle strength and social functioning. Conclusions: We found that perceived activity can provide useful information about pain, knee muscle weakness and social functioning, and vice versa.
Keywords: Athletic Injuries; Knee; koleno; poškodbe; Quality of Life; rehabilitacija; Rehabilitation; Sports; športne poškodbe; telesna dejavnost; vocational rehabilitation